2018
DOI: 10.3892/ol.2018.9359
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus X protein promotes epithelial‑mesenchymal transition and metastasis in hepatocellular carcinoma cell line HCCLM3 by targeting HMGA2

Abstract: Chronic hepatitis B virus (HBV) infection is a major risk factor for hepatocellular carcinoma (HCC), and HBV X protein (HBx) serves an essential role in the development of HCC. However, its mechanism remains to be elucidated. The aim of the present study was to investigate the role and mechanism of the HBx protein in the epithelial-mesenchymal transition (EMT) and metastasis of HCC. The HCCLM3 cell line was transfected with a HBx-expressing vector. The effects of HBx overexpression on proliferation, migration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…23 The role of HMGA2 in HCC has also been addressed in previous studies. It is reported that hepatitis B virus X protein promotes EMT of HCC cells by targeting HMGA2; 37 Meanwhile, a recent study have shown that the HMGA2-sh-3p20 fragment in the 3ʹUTR of HMGA2 mRNA promotes the growth of HCC cells by up-regulating HMGA2. 38 However, whether EGOT affects the expression of HMGA2 has not been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…23 The role of HMGA2 in HCC has also been addressed in previous studies. It is reported that hepatitis B virus X protein promotes EMT of HCC cells by targeting HMGA2; 37 Meanwhile, a recent study have shown that the HMGA2-sh-3p20 fragment in the 3ʹUTR of HMGA2 mRNA promotes the growth of HCC cells by up-regulating HMGA2. 38 However, whether EGOT affects the expression of HMGA2 has not been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Ã P < 0.05; ÃÃÃ P < 0.001; ÃÃÃÃ P < 0.0001. highest and lowest in HCC-LM3 compared to the other two HCC cell lines, respectively. Due to the high invasion capacity of HCC-LM3 cells (Zha et al, 2018), this suggested that miR-221-3p and miR-375 could be critical regulators of HCC cell invasion. HepG2.2.15 is an HCC cell line that carries and secretes HBV particles.…”
Section: The Expression Level Of Mir-221-3p and Mir-375 In Hcc Cells mentioning
confidence: 99%
“…Research showed that HBx could induce HMGA2 by regulating EMT, subsequently leading to HCC cell invasion. 37 These evidence suggest that HBx might regulate YAP1 in the EMT process. Indeed, we proved that HBx regulated promoter region of YAP was located at nt −348 through luciferase reporter gene assays.…”
Section: Dovepressmentioning
confidence: 92%